2014
DOI: 10.1103/physrevlett.113.024507
|View full text |Cite|
|
Sign up to set email alerts
|

Experiments of Drops Impacting a Smooth Solid Surface: A Model of the Critical Impact Speed for Drop Splashing

Abstract: Making use of experimental and theoretical considerations, in this Letter we deduce a criterion to determine the critical velocity for which a drop impacting a smooth dry surface either spreads over the substrate or disintegrates into smaller droplets. The derived equation, which expresses the splash threshold velocity as a function of the material properties of the two fluids involved, the drop radius, and the mean free path of the molecules composing the surrounding gaseous atmosphere, has been thoroughly va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

40
377
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(418 citation statements)
references
References 33 publications
40
377
1
Order By: Relevance
“…This dynamics is similar to that following a mechanical impact such as on a solid substrate or a pillar, which has been studied thoroughly (see e.g. Clanet et al 2004;Yarin 2006;Villermaux & Bossa 2011;Kolinski et al 2012;Riboux & Gordillo 2014;Josserand & Thoroddsen 2016), including a few studies on the fragmentation of the drop (Villermaux 2007;Xu et al 2007;Villermaux & Bossa 2009, 2011Riboux & Gordillo 2014). A laser proves to be an adequate tool to vary the extension of the impact without arXiv:1512.02415v1 [physics.flu-dyn] 8 Dec 2015…”
mentioning
confidence: 82%
“…This dynamics is similar to that following a mechanical impact such as on a solid substrate or a pillar, which has been studied thoroughly (see e.g. Clanet et al 2004;Yarin 2006;Villermaux & Bossa 2011;Kolinski et al 2012;Riboux & Gordillo 2014;Josserand & Thoroddsen 2016), including a few studies on the fragmentation of the drop (Villermaux 2007;Xu et al 2007;Villermaux & Bossa 2009, 2011Riboux & Gordillo 2014). A laser proves to be an adequate tool to vary the extension of the impact without arXiv:1512.02415v1 [physics.flu-dyn] 8 Dec 2015…”
mentioning
confidence: 82%
“…Since then, numerous studies have investigated the mechanism by which gas pressure influences the splash dynamics. These studies have involved and combined theoretical, experimental and numerical approaches (Korobkin et al 2008;Mandre et al 2009;Mani et al 2010;Hicks & Purvis 2010;Duchemin & Josserand 2011;Driscoll & Nagel 2011;Kolinski et al 2012;Duchemin & Josserand 2012;Hicks et al 2012;Riboux & Gordillo 2014;Kim et al 2014;Liu et al 2015;Guo et al 2016). It has been demonstrated that splashing was closely linked with the dynamics of the thin film of gas, either beneath the drop before impact but also during the fast spreading of the drop after impact.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, even the very basic question of which part of air plays the essential role is completely unknown. Moreover, the analysis from classical aerodynamics (18) indicates that the viscous effect from air totally dominates any pressure influence, whereas the experiment contradictorily revealed a strong pressure dependence (15). Even more puzzling, it was revealed that the speed of sound in air plays an important role in splashing generation (15), although the impact speed is typically 10-100 times slower!…”
mentioning
confidence: 99%
“…Splashing is crucial in many important fields, such as the sprinkler irrigation and pesticide application in agriculture, ink-jet printing and plasma spraying in printing and coating industries, and spray cooling in various cooling systems; therefore its better understanding and effective control may make a far-reaching impact on our daily life. Starting in the 19th century, extensive studies on drop impact and splashing have covered a wide range of control parameters, including the impact velocity, drop size, surface tension, viscosity, and substrate properties (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), and various splashing criteria have been proposed and debated (13)(14)(15)(16)(17)(18). Nevertheless, at the most fundamental level the generation mechanism of splashing remains a big mystery.…”
mentioning
confidence: 99%